Fabrication and control of a test platform for vision-based attitude estimation system - de Ocampo, Reya Angela S.; Uy, Kathlyn Charmaine J. (2008.)
Bipedal robots are developed today for its ability to cover terrains which other mobile robots cannot. Maintaining the balance of this inherently unstable system is one of the first and essential steps in making the bipedal robot useful. The attitude of the bipedal robot must be well-estimated in order for its actuators to react to changes in tilt and rotation of the system and retain its stability. Accelerometers and gyroscopes are among the most commonly used implementations of attitude estimators. We aim to develop a test platform that will be used for developing image processing algorithms to extract relevant balancing information from real-time images. An inverted pendulum connected to a moving base via a universal joint will be used to approximate the bipedal system. However, this project is constrained such that the inverted pendulum only falls along a single axis. The test platform accepts angle measurement from the CMUcam3 and actuates the motors to balance the inverted pendulum. To test the capability of the system in balancing the inverted pendulum itself, an angle sense circuit consisting of a potentiometer connected to the base of the rod was used as feedback . The varying voltage output of the angle sense circuit is mapped to a ±15° variation of angles wit respect to upright position. The microcontroller board actuates the motors of the test system to balance the inverted pendulum.
Undergraduate Student Project (B.S. CoE)--University of the Philippines, Diliman.
Keywords: Robots -- Control systems -- Design and construction; Image processing -- Digital techniques; Bipedal robots; Attitude estimation system